A case of ulcerative colitis with digital arterial thrombosis - Çağatay Arslan; Mehmet İşler and Güçhan Alanoğlu (Turkish Journal of Gastroenterology, 2019)
Thromboembolic events are rare in the course of ulcerative colitis and related with the activity of the disease. These complications are especially seen in young patients and cause high mortality and morbidity. Arterial thrombotic complications are less frequent and are usually seen after a surgical procedure. Here, we present a 36-year-old man with active ulcerative colitis presenting via digital arterial thrombosis and digital necrosis that was not associated with a surgical procedure. Turkish Başlık: Parmak arterlerinde tromboz gelişen ülseratif kolit olgusu Anahtar kelimeler: Ülseratif kolit, parmak nekrozu, parmak arter trombozu Ülseratif kolit seyri sırasında tromboembolik olaylar nadirdir ve hastalık aktivitesi ile ilişkilidir. Bu komplikasyonlar genellikle genç hastalarda görülür ve yüksek oranda morbidite ve mortaliteye neden olur. Arteriyal trombotik olaylar daha nadir görülür ve genellikle cerrahi girişim sonrasında gelişir. Cerrahi girişim ile ilişkili olmayan parmak arterlerinde arteryal tromboz ve parmak nekrozu ile başvuran 36 yaşında aktif ülseratif kolit olgusu sunulmuştur.